Automated Oxygen Delivery in Hospitalized Patients with Acute Respiratory Failure: A Pilot Study. (3rd February 2019) - Malli, Foteini; Boutlas, Stelios; Lioufas, Nick; Gourgoulianis, Konstantinos I.
Abstract : Background and Objectives . Despite its' proven benefits, oxygen therapy may be complicated with potential adverse events such as hypoxemia or hyperoxia-driven hypercapnia. Automated oxygen delivery systems may aid in avoiding these complications. The scope of the present study is to test the efficacy and safety of a new automated oxygen delivery device. Methods . This study included 23 patients with acute respiratory failure (ARF) hospitalized in the Respiratory Medicine Department of the University Hospital of Larissa. Both patients with purely hypoxemic or hypercapnic ARF were included. Automated oxygen administration was performed with Digital Oxygen Therapy, a new closed-loop system designed to automatically adjust oxygen flow according to target oxygen saturation (SpO2 ) of 88–92% for hypercapnic patients and 92–96% for purely hypoxemic patients with ARF. The device was applied for 4 hours. Arterial blood gas analysis was performed at 1 hour and 3 hours following the device application. Results . Mean age was 72.91 ± 13.91 years. Twelve patients were male, and 11 were female. The majority of patients suffered from hypercapnic respiratory failure (n = 13, 56.5%). At 1 hour and 3 hours, SpO2 and PaO2 displayed excellent correlation (p < 0.001, r  = 0.943, andp < 0.001, r  = 0.954, respectively). We did not observe any adverse events associated with the device. Conclusions . Our results indicate that automated oxygen treatment is feasible and safe in hospitalized patients with acute respiratory failure. Further studies are required in order to assess the long-term effects of automated oxygen delivery systems.